Tyrosinase and laccase biosensors based on graphene- gold-chitosan nanocomposite-modified screen-printed carbon electrode for phenolic compounds detection - Fartas, Fuzi Mohamed (2018)
Phenolic compounds are among the most pollutants present in ground and surface water. These compounds consider potentially harmful to human health and showing adverse effects on the environment. Bisphenol A (BPA) is one of phenolic compounds which is widely used as a raw material for common products, including food containers, an inner liner for food cans, beverage cans, water bottles and baby bottles. The hazard effect exposure to BPA released from these materials is increasing due to its endocrine-disrupting potential can cause several health diseases such as cancers, developmental problems and heart disease. The conventional methods used for detecting these pollutants suffered some limitations such as expensive instrumentation, time-consuming and not suitable for in-situ monitoring. In this study, electrochemical biosensors were fabricated based on immobilization of tyrosinase and laccase onto graphene-decorated gold nanoparticle/chitosan (Tyr/Gr-Au-Chit and Lacc/Gr-Au-Chit) nanocomposite-modified screen-printed carbon electrode (SPCE) for the detection of phenolic compounds. The gold nanoparticles (AuNPs) decorated graphene nanosheets (Gr) in combination with chitosan was deposited onto SPCE via drop casting technique. The tyrosinase and laccase enzyme was immobilized onto the modified electrode via physical adsorption. The prepared nanocomposite was characterized by using Fourier Transform Infrared Spectroscopy (FTIR), Raman spectroscopic, Transmission Electron Microscopy (TEM), X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and Energy dispersive X-ray (EDX). The FTIR spectra for Tyr/Gr-Au-Chit and Lacc/Gr-Au-Chit show new peaks at 1639 cm-1 and 1543 cm-1 for amide I and amide II are due to –C=O stretching, C–N stretching, and –N–H bending of vibration bands of amide groups of both enzymes which proved the successful immobilization of the enzymes onto the Gr-Au-Chit/SPCE nanocomposite matrix. The increased in the intensity ratio of Raman spectra (ID/IG = 0.58) for Gr-Au/Chit compared to Gr-Au substrate (ID/IG = 0.34) demonstrated that the Gr-Au/Chit nanocomposite was successfully prepared. Electrochemical characterization of the modified electrodes revealed that the nanocomposite have increased its electro-active surface area and conductivity. The electroactive surface area (A) of bare SPCE and Gr-Au-Chit/SPCE was calculated to be 0.091 cm2 and 0.488 cm2, respectively. While the electron transfer resistance (Rct) at the bare SPCE and Gr-Au-Chit/SPCE was found to be (36 KΩ) and (89 Ω), respectively. The modified SPCEs showed a remarkable activity which attributed to the excellent conductivity, large surface area, electrocatalytic activity and good synergetic effect of the bio-nanocomposite films towards phenol and bisphenol A. The fabricated Tyr/Gr-Au-Chit biosensor was applied for the voltammetric detection of phenol in water sample by differential pulse voltammetry (DPV). Under the optimum conditions, the Tyr/Gr-Au-Chit based biosensor displays a linear calibration curve in the phenol concentration range of 0.05 to 15.00 μM with sensitivity of 0.62 μA/μM and limit of detection (LOD) of 0.02 μM. While differential pulse voltammetric technique was employed for second fabricated biosensor (Lacc/Gr-Au-Chit) for bisphenol A detection. Under the optimum conditions, the Lacc/Gr-Au-Chit based biosensor gave linear calibration curve in the bisphenol A concentration range of 0.05 to 12.00 μM with sensitivity of 0.27 μA/μM and detection limit of 0.02 μM. The proposed methods showed good selectivity of target analytes even in the presence of some foreign ions. The fabricated biosensor (Tyr/Gr-Au-Chit) was successfully applied for the determination of phenol in lake water sample while Lacc/Gr-Au-Chit was successfully applied for the determination of bisphenol A in different types of commercial plastic products with satisfactory recovery results from 96.40% to 101.16% and 98.31% to 102.92%, which comparable to HPLC technique. These findings suggests that the developed biosensors have a promising potential for the detection of phenol and bisphenol A in water sample and plastic samples for environmental monitoring and industrial quality control.